Poets and prophets of the Resistance : intellectuals and the origins of El Salvador's civil war - Chávez, Joaquín Mauricio
"Poets and Prophets of the Resistance offers a ground-up history and fresh interpretation of the polarization and mobilization that brought El Salvador to the eve of civil war in 1980. Challenging the dominant narrative that university students and political dissidents primarily formed the Salvadoran guerrillas, Joaquín Chávez argues that El Salvador's socioeconomic and political crises of the 1970s fomented a groundswell of urban and peasant intellectuals who collaborated to spur larger revolutionary social movements. Drawing on new archival sources and in-depth interviews, Poets and Prophets of the Resistance contests the idea that urban militants and Roman Catholic priests influenced by Liberation Theology single-handedly organized and politicized peasant groups. Chávez shows instead how peasant intellectuals acted as political catalysts among their own communities first, particularly in the region of Chalatenango, laying the groundwork for the peasant movements that were to come. In this way, he contends, the Salvadoran insurgency emerged in a dialogue between urban and peasant intellectuals working together to create and execute a common revolutionary strategy--one that drew on cultures of resistance deeply rooted in the country's history, poetry, and religion. Focusing on this cross-pollination, this book introduces the idea that a 'pedagogy of revolution' originated in this historical alliance between urban and peasant, making use of secular and Catholic pedagogies such as radio schools, literacy programs, and rural cooperatives. This pedagogy became more and more radicalized over time as it pushed back against the increasingly repressive structures of 1970s El Salvador. Teasing out the roles of little-known groups such as the politically active 'La Masacuata' literary movement, the contributions of Catholic Action intellectuals to the New Left, and the overlooked efforts of peasant leaders, Poets and Prophets of the Resistance demonstrates how trans-class political and cultural interactions drove the revolutionary mobilizations that anticipated the Salvadoran civil war"--